2016
DOI: 10.1002/2016jc011771
|View full text |Cite
|
Sign up to set email alerts
|

Size characteristics of chromophoric dissolved organic matter in the Chukchi Sea

Abstract: With the Arctic warming, terrestrial input plays a more important role in carbon cycle in the Arctic Ocean than before. Chromophoric dissolved organic matter (CDOM) as a tracer of terrestrial dissolved organic matter (tDOM) becomes more valuable in elucidating the source and compositions of DOM. Although measurements of DOM in the Arctic Ocean have been widely reported, characteristics of high molecular weight colloids are still poorly understood. In this study, the bulk absorbance and size fractograms of CDOM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 74 publications
2
5
0
Order By: Relevance
“…(1.62-2.52 kDa) were reported for colloidal DOM in Chukchi Sea (Lin et al, 2016). The average MW reported in Beaufort Sea agreed with values reported for fulvic acids (Beckett et al, 1987;Guéguen and Cuss, 2011), confirming that fulvic acids are good proxy for marine DOM (Tipping et al, 2015).…”
Section: Molecular Weight Depth Distributionsupporting
confidence: 79%
See 3 more Smart Citations
“…(1.62-2.52 kDa) were reported for colloidal DOM in Chukchi Sea (Lin et al, 2016). The average MW reported in Beaufort Sea agreed with values reported for fulvic acids (Beckett et al, 1987;Guéguen and Cuss, 2011), confirming that fulvic acids are good proxy for marine DOM (Tipping et al, 2015).…”
Section: Molecular Weight Depth Distributionsupporting
confidence: 79%
“…The simultaneous multi wavelength measurements of the online absorbance detector allow us to accurately determine of each of the four macromolecules in a single injection. The retention time at 254 nm was used to estimate the CDOM MW at peak maximum intensity (Guéguen and Cuss, 2011;Lin et al, 2016;Stolpe et al, 2010Stolpe et al, , 2014. For example, a typical calibration recorded at 254 nm was log (Time) = (0.1634 ± 0.0086) * Log (MW) + (0.4831 ± 0.0228) (r 2 = 0.999).…”
Section: Asymmetrical Flow Field-flow Fractionationmentioning
confidence: 99%
See 2 more Smart Citations
“…The outflow time of nanoparticles (Figure 3) was mainly concentrated at 10-16 min, corresponding to the outflow interval of C 1 , which further verified that seawater nanomaterials were mainly composed of small-sized particles. This is consistent with an earlier study which showed that, in the Chukchi Sea, the colloidal materials were primarily dominated by small-sized particles (55.4%) (Lin et al, 2016). Stolpe et al (2014) and Zhou et al (2016) obtained similar findings in the Mississippi River and in small rivers in the Gulf of Mexico, which they attributed to the important contribution of small-sized terrestrial humus to river nanoparticles.…”
Section: Size Distribution Of Nanoparticlessupporting
confidence: 92%